A female with mucocutaneous telangiectases and portal hypertension: A case report of osler-weber-rendu syndrome - Vidhi S Chandibhamar; Bhagirath R Patel; Ani Patel; Jignaben K Padhiyar (Wolters Kluwer Medknow Publications, 2021)
Osler-Weber-Rendu syndrome, also known as hereditary hemorrhagic telangiectasia, is a rare autosomal dominant disorder manifested by telangiectases of the skin and mucous membranes and arteriovenous malformations of various organ systems. We report a case of 45-year-old postmenopausal woman who presented to dermatology department for evaluation of compressible vascular lesion involving bilateral palms and oral cavity for the past 3 months' duration. On further evaluation, she was found to have portal hypertension and multiple cavernoma formation on place of portal vein.